FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BUANG AIR BESAR SEMBARANGAN (BABS) - Deby Puspitasari; Titin Nasiatin (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Open defecation (BABS) behaviour is an act of disposing of feces in fields, forests, bushes, rivers, beaches or other open areas and allowed to spread to contaminate the environment, soil, air and water, causing new problems that can cause problems. endanger human health. This study aims to determine the relationship between open defecation (BABS) behavior with latrine ownership, knowledge and attitudes in the Kasunyatan Village, the working area of ​​the Kasemen Health Center. Methods: The research design used was cross sectional with a sample of 93 respondents. The sampling method was taken by simple random sampling. Data analysis using univariate and bivariate. Questionnaire was used to collect the primary data. While the secondary data was obtained from the profile data of the Kasemen Health Center in 2018. Results: There were people who practice open defecation (35.5%), a total of 59 (63.4%)people did not have the qualified latrine, 47.3% have poor knowledge, and 40.9% have bad attitudes. A significant relationship was found between eligible latrine conditions (p=0.000), knowledge (p=0.0001) and attitudes (p=0.000) with open defecation behavior. Conclusion: Unqualified latrine conditions, knowledge and attitudes of respondents affect open defecation behavior